Result Representation of Congenital Hypothyroid Screening (CHS) Based on Area Topography in Bandar Lampung City in May-October 2019 - Nabila Rayhan Yasmin; Rodiani Rodiani; Intanri Kurniati; Nisa Karima (Faculty of Medicine, Public Health, and Nursing, 2022)
Congenital Hypothyroid Screening (CHS) is a screening test performed on neonates to detect Congenital Hypothyroidism (CH). Screening is important to prevent delays in the diagnosis and management of CH. Until now, Indonesia does not have data on the result representation of national and regional CH based on regional topography. This descriptive research used a cross-sectional design. The research was conducted at the Public Health Office of Bandar Lampung. This research used the secondary data of the incidence of CHS, CHS service provider health facilities, and babies born alive in May-October 2019. The results’ representation is then grouped by subdistrict and topography of the region (tidal, choppy to wavy, and hilly to mountainous). The number of CH incidents was highest in Panjang District (235 data) and there was no CHS data in Enggal Subdistrict. The result representation was the highest in Tanjung Karang Timur District (41%). An overview of the result representation by sub- district was obtained by 18%. Overview of the result representations were in tidal topographic areas with 24%, choppy to wavy had a percentage of 18%, and the lowest hilly to mountainous areas had 15%. The topographical areas that have the highest result representation of CHS results are tidal areas, while the lowest are hilly to mountainous areas.